Transcriptomic profiling of Tibetan highland fish (Gymnocypris przewalskii) in response to the infection of parasite ciliate Ichthyophthirius multifiliis. Issue 70 (November 2017) - Tian, Fei; Tong, Chao; Feng, Chenguang; Wanghe, Kunyuan; Zhao, Kai
Abstract: Gymnocypris przewalskii is a native cyprinid in the Lake Qinghai of the Qinghai-Tibetan Plateau. G. przewalskii is highly susceptible to the infection of a parasite, Ichthyophthirius multifiliis, in the artificial propagation and breeding. To better understand the host immune reaction to I. multifiliis infection, we characterize the gene expression profiles in the spleen of healthy and I. multifiliis infected G. przewalskii by RNA-seq. Totally, the transcriptomic analysis produces 463, 031, 110 high quality reads, which are assembled to 213, 538 genes with N50 of 1918 bp and the average length of 1205 bp. Of assembled genes, 90.52% are annotated by public databases. The expression analysis shows 744 genes are significantly changed by the infection of I. multifiliis, which are validated by qRT-PCR with the correlation coefficient of 0.896. The differentially expressed genes are classified into 689 GO terms and 230 KEGG pathways, highlighting the promoted innate immunity in I. multifiliis infected G. przewalskii at 2 days post infection. Our results pinpoint that the up-regulated genes are enriched in TLR signaling pathway, inflammatory response and activation of immune cell migration. On the contrary, complement genes are down-regulated, indicating the evasion of host complement cascades by I. multifiliis . The repressed genes are also enriched in the pathways related to metabolism and endocrine, suggesting the metabolic disturbance in I. multifiliis treated G. przewalskii . In summary, the present study profiles the gene expression signature of G. przewalskii in the responses to I. multifiliis infection, and improves our understanding on molecular mechanisms of host-parasite interaction in G. przewalskii, which focuses the crucial function of TLRs, cytokines and complement components in the host defense against I. multifiliis . Highlight: We evaluated transcriptomic alterations in G. przewalskii induced by I. multifiliis infection. Totally, 463, 031, 110 high quality reads were produced by RNA-seq, which were finally assembled to 213, 538 genes. After I. multifiliis challenge, 744 genes were significantly differentially expressed in the spleen of G. przewalskii . The DEGs were enriched in the TLR signaling pathway, complement cascade, and inflammation. The parasite might develop the strategy to repress genes in complement cascades in G. przewalskii .